Aqueous zinc ion battery electrolyte, preparation method and application thereof, and aqueous zinc battery
By adding borate ester additives to the electrolyte of the aqueous zinc ion battery, the interface protective layer and coordination with zinc ions are formed, and the problems of the battery in zinc dendrites growth, hydrogen evolution reaction and interface corrosion are solved, and the cycling performance of the battery is significantly improved.
Patent Information
- Application Number
- CN202411855918.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
Water-based zinc ion batteries have insufficient coulomb efficiency and reversibility in issues such as zinc dendrites growth, hydrogen evolution reaction and continuous interface corrosion, which limits their cycle life and practical applications.
Borate ester additives are used to improve the interface stability between the electrode and the electrolyte by the interface protective layer formed on the surface of the zinc negative electrode and the direct coordination with the zinc ions, thereby optimizing the reversible deposition/peeling behavior of zinc ions.
In the case of extremely low usage, the zinc negative electrode exhibits excellent cycle reversibility and interface stability, which significantly improves the cycling performance of the battery.
Smart Images

Figure CN119674277A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of aqueous zinc ion technology, and in particular to an aqueous zinc ion battery electrolyte, a preparation method thereof, an application thereof, and an aqueous zinc battery. Background Art
[0002] Aqueous zinc-ion battery is a new type of energy storage device that uses zinc ions to perform charge and discharge reactions in a water-based electrolyte to store and release energy. Its main principle is that during the battery operation, during the discharge process, zinc metal (negative electrode) will oxidize and release zinc ions (Zn 2+ ) and enter the electrolyte. At the same time, the electrons released by the negative electrode flow through the external circuit and reach the positive electrode. Taking the intercalation type positive electrode as an example, the zinc ions on the positive electrode side will be embedded in the positive electrode material, and the positive electrode material will accept electrons to maintain electrical neutrality. Thereby realizing the discharge process of the battery. During the charging process, the external power supply drives electrons to flow to the negative electrode, and the zinc ions (Zn2+) accept electrons at the negative electrode and are reduced to zinc metal and deposited on the surface of the negative electrode. At the same time, the positive electrode material loses electrons, and the zinc ions in the intercalation type positive electrode are released, thereby realizing the charging of the battery. The zinc electrode plays an important role. During discharge, the zinc electrode is oxidized into zinc ions (Zn 2+ ), while releasing electrons, which flow through the external circuit to complete the conversion of electrical energy; during charging, the electrons transmitted from the external circuit react with zinc ions, reducing them to zinc electrodes, while storing electrical energy. Aqueous zinc-ion batteries have great potential in the storage and application of renewable energy due to their high energy density, long cycle life, low cost and environmental protection.
[0003] Aqueous zinc-ion batteries are considered promising next-generation energy storage devices due to their high safety, low cost, and high theoretical capacity, especially considering their great potential for large-scale energy storage. However, many issues such as Zn dendrite growth, hydrogen evolution reaction (HER), and continuous interface corrosion reduce the coulombic efficiency and reversibility of the battery and limit its cycle life, resulting in great uncertainty in its practical application. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide an aqueous zinc ion battery electrolyte and its preparation method, application and aqueous zinc battery, so as to improve the electrode stability, improve the interface stability between the positive electrode and the electrolyte, and thus make the battery have excellent cycle performance.
[0005] The first aspect of the present application provides an aqueous zinc ion battery electrolyte, comprising a solvent, a zinc salt and an additive, wherein the additive is a borate derivative.
[0006] In any embodiment, the borate derivative is one or more of trimethyl borate, triethyl borate, tri(trimethylsilyl)borate, diethanolamine borate, triethanolamine borate, and amino alcohol borate.
[0007] In any embodiment, the zinc salt is one or more of ZnSO4, ZnCl2, Zn(ClO4)2, Zn(NO3)2, Zn(CF3SO3)2, Zn(CH3COO)2 and Zn(TFSI)2; the solvent is deionized water. Borate additives are used to improve the electrochemical performance of batteries using zinc salts such as zinc perchlorate as electrolytes.
[0008] In any embodiment, the concentration of the zinc salt is 0.5 mol / L to 3 mol / L.
[0009] In any embodiment, the concentration of the additive in the electrolyte is 0.1 mM / L to 50 mM / L. The performance of the electrolyte is improved.
[0010] The second aspect of the present application provides a method for preparing an aqueous zinc ion battery electrolyte. At 25°C, a zinc salt is added to deionized water and stirred until fully dissolved to obtain a basic zinc salt electrolyte. An additive is then added to the obtained basic zinc salt electrolyte, and then stirred until fully dissolved to obtain an electrolyte modified with a borate derivative of an aqueous zinc ion battery.
[0011] The third aspect of the present application provides an application of an aqueous zinc ion battery electrolyte, and the application of the aqueous zinc ion battery electrolyte or the electrolyte obtained by the preparation method in a Zn / / Zn symmetric battery, a Zn / / Cu half-cell or an aqueous zinc ion full battery.
[0012] The fourth aspect of the present application provides an aqueous zinc battery, including a battery shell, a positive electrode, a diaphragm, an electrolyte, a negative electrode, a gasket and a spring, wherein the positive electrode and the negative electrode are relatively arranged in the battery shell, the electrolyte is arranged in the battery shell, the diaphragm is arranged in the electrolyte between the positive electrode and the negative electrode, the gasket and the spring are arranged in the battery shell, and the spring is used to provide a certain elastic pressure inside the battery to ensure good contact between the positive and negative electrodes of the battery and the external circuit. The thickness is usually selected from 1.1mm and 1.2mm; the thickness of the gasket is usually selected from 0.5mm and 1.0mm, which is used to adjust the internal pressure of the battery. The spatial structure is used to improve the performance of the battery; the battery shell is CR2025 ("20" represents that the diameter of the battery is 20mm, and the last two digits "25" represent that the thickness of the battery is 2.5mm), the positive electrode and the negative electrode are both high-purity zinc foil, the thickness of the high-purity zinc foil is 0.02-0.1mm, and the diameter is 12-16mm, the diaphragm is a glass fiber diaphragm, the diameter of the diaphragm is 16mm, and the amount of the electrolyte is 80-150μL; the battery is pressurized to 50MPa, and the pressure is maintained for 10 to 30s to complete the assembly of the Zn / / Zn symmetrical battery. The thickness of the zinc sheet is usually selected from 0.02mm, 0.05mm, 0.08mm, and 0.1mm; the diameter of the zinc electrode sheet is usually selected from 12mm, 14mm, and 16mm.
[0013] A water-based zinc battery comprises a battery shell, a positive electrode, a diaphragm, an electrolyte, a negative electrode, a gasket and a spring, wherein the positive electrode and the negative electrode are arranged in the battery shell relative to each other, the electrolyte is arranged in the battery shell, the diaphragm is arranged in the electrolyte between the positive electrode and the negative electrode, and the gasket and the spring are arranged in the battery shell; the battery shell is CR2025, the positive electrode is a high-purity copper foil with a thickness of 5-20 μm and a diameter of 12-16 mm, the negative electrode is a high-purity zinc foil with a thickness of 0.02-0.1 mm and a diameter of 12-16 mm, the diaphragm is a glass fiber diaphragm with a diameter of 16 mm, and the amount of the electrolyte is 80-150 μL; the battery is pressurized to 50 MPa, and the pressure is maintained for 10 to 30 seconds to complete the assembly of the Zn / / Cu half-cell.
[0014] A water-based zinc battery comprises a battery shell, a positive electrode, a diaphragm, an electrolyte, a negative electrode, a gasket and a spring, wherein the positive electrode and the negative electrode are arranged oppositely in the battery shell, the electrolyte is arranged in the battery shell, the diaphragm is arranged in the electrolyte between the positive electrode and the negative electrode, and the gasket and the spring are arranged in the battery shell; the base material of the positive electrode is a stainless steel mesh, on which the positive electrode material is cast, the negative electrode is one of high-purity zinc foil, zinc powder and foamed zinc, with a thickness of 0.02-0.1 mm and a diameter of 12-16 mm, the diaphragm is a glass fiber diaphragm with a diameter of 16 mm, the battery shell model is CR2025, and the electrolyte is used in an amount of 80-150 μL; the battery is pressurized to 50 MPa, and the pressure is maintained for 10 to 30 seconds to complete the assembly of the Zn / / I2 full battery.
[0015] In any embodiment, the positive electrode material is one of iodine, manganese-based oxides, vanadium-based materials, Prussian blue analogs, carbon felt or graphite felt.
[0016] In any embodiment, the positive electrode is prepared by mixing the positive electrode material, Ketjen black and PVDF binder with NMP solvent in a weight ratio of 7:2:1 or 8:1:1 to form a uniform slurry, casting the slurry on a stainless steel wire mesh, and finally vacuum drying in a 40°C oven for 24 hours.
[0017] In any embodiment, the loading amount of the positive electrode material on the substrate material is about 1.5 to 2.0 mg·cm -2 .
[0018] Beneficial effects of the present invention: This application uses an aqueous zinc ion battery electrolyte additive, which has a simple preparation process and low cost. When used in extremely low dosage, the zinc negative electrode exhibits excellent cycle reversibility and interface stability; the electrolyte additive uses a borate compound containing a borate functional group. The boron element contained in the functional group has an empty p orbital, which can provide a Lewis acid functional site, coordinate with the negatively charged oxygen element, and form a three-dimensional spatial structure with three oxygen-containing sites. Due to the above-mentioned specific molecular structure, the compound can not only adsorb onto the surface of the zinc negative electrode to reduce the number of free water molecules adsorbed on the zinc surface, but also react chemically with zinc atoms to form an in-situ interface protective layer, further inhibiting the occurrence of side reactions such as corrosion and passivation. On the other hand, zinc ions are usually present in water-based solutions in the form of hydrated zinc ions (Zn(H2O)6 2+ ), the oxygen-containing sites of borate additives can directly coordinate with zinc ions, reduce the number of water molecules and zinc ions, reconstruct the solvation structure of hydrated zinc ions, and optimize the reversible deposition / stripping behavior of zinc ions. The preparation process of the electrolyte is simple and low-cost. When the dosage is extremely low, the zinc negative electrode exhibits excellent cycle reversibility and interface stability, which makes the battery have excellent cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the SEM image of the zinc negative electrode of this application after cycling in the electrolyte prepared with Zn(ClO4)2 salt.
[0020] Figure 2 This is the SEM image of the zinc negative electrode of this application after cycling in the electrolyte prepared with Zn(ClO4)2 salt and TEAB additive.
[0021] Figure 3 This is the SEM image of the zinc negative electrode of this application after cycling in the electrolyte prepared with ZnSO4 salt.
[0022] Figure 4 This is the SEM image of the zinc negative electrode of this application after cycling in the electrolyte prepared with ZnSO4 salt and TEAB additive.
[0023] Figure 5 The electrolyte prepared by Zn(ClO4)2 salt and TEAB additive in this application is 10mA·cm in Zn / / Zn symmetric battery -2 、10mAh·cm -2 Cyclic performance diagram under 24-hour conditions.
[0024] Figure 6 The electrolyte prepared by ZnSO4 salt and TEAB additive in the present application is 10mA·cm in Zn / / Zn symmetric battery -2 、10mAh·cm -2 Cyclic performance diagram under 24-hour conditions.
[0025] Figure 7 For the Zn / / Zn symmetric cell of this application, the electrolyte prepared with 5 mM / L TEAB additive and 2 M Zn(ClO4)2 salt was used at 10 mA cm -2 -10mAh cm -2 Electrochemical data measured at current density and areal capacity.
[0026] Figure 8 For this application, the Zn / / Cu half-cell uses an electrolyte prepared with 5 mM / L TEAB additive and 2 M Zn(ClO4)2 at 1 mA cm -2 -1mAh cm -2 Electrochemical data measured at current density and areal capacity.
[0027] Fig. 9 The electrochemical data of the electrolyte prepared with 5mM / L TEAB additive and 2M Zn(ClO4)2 for the Zn / / I2 full cell of this application was measured at a current density of 0.1A / g. DETAILED DESCRIPTION
[0028] Hereinafter, the aqueous zinc ion battery electrolyte and its preparation method, application and implementation mode of the aqueous zinc battery of the present application will be specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0029] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0030] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0031] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0032] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0033] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0034] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0035] Aqueous zinc-ion batteries have a series of problems such as Zn dendrite growth, hydrogen evolution reaction (HER), and continuous interface corrosion, which reduce the coulombic efficiency and reversibility of the battery, limit its cycle life, and lead to great uncertainty in its practical application. In order to solve the above problems, the researchers of this application have proposed various strategies to improve the reliability of zinc anodes in aqueous solutions, including the design of electrode structure, modification of electrode interface, and engineering of electrolytes. Among these strategies, designing electrolyte formulations is a top priority, especially the addition of functional additives, which provides a simple and effective method with significant scalability. At present, the main types of additives include organic additives and inorganic additives. However, the continuous consumption of organic additives during the structural rearrangement of zinc anodes poses challenges, resulting in the formation of thick and unstable interface layers at zinc anodes. And some organic additives are related to the safety hazards of aqueous zinc-ion batteries, causing absolutely safe aqueous electrolytes to become less safe. It is also difficult for inorganic additives to establish a consistent and uniform interface layer on the surface of zinc anodes. Therefore, it is necessary to explore new additives to form a uniformly distributed interface phase on the surface of zinc anodes. Borate ester additives contain borate ester functional groups (-B(OR)2), where R can be different organic groups such as alkyl and aryl groups. The boron element containing an empty p orbital reacts chemically with the Zn atom to form a stable SEI to protect the negative electrode from contact with water molecules, thereby inhibiting the occurrence of side reactions, while allowing zinc ions to be freely inserted and extracted, thereby improving the interface stability between the electrode and the electrolyte; the oxygen-containing sites of the borate ester additives can reduce the number of water molecules and zinc ions coordinated by directly coordinating with zinc ions, reconstruct the solvation structure of hydrated zinc ions, and thus enable aqueous zinc ion batteries to have excellent cycle performance.
[0036] An aqueous zinc ion battery electrolyte comprises a solvent, a zinc salt and an additive, wherein the additive is a borate derivative.
[0037] In some embodiments, the borate derivative is one or more of trimethyl borate, triethyl borate, tri(trimethylsilyl)borate, diethanolamine borate, triethanolamine borate, and amino alcohol borate.
[0038] In some embodiments, the zinc salt is one or more of ZnSO4, ZnCl2, Zn(ClO4)2, Zn(NO3)2, Zn(CF3SO3)2, Zn(CH3COO)2 and Zn(TFSI)2; and the solvent is deionized water.
[0039] In some embodiments, the concentration of the zinc salt is 0.5 mol / L to 3 mol / L.
[0040] As the salt concentration increases, the viscosity of the electrolyte usually increases, affecting the diffusion rate of ions. Higher viscosity may hinder the movement of ions in the electrolyte and reduce the kinetic performance of the battery. If the salt concentration is too low, there will be too few ions that can move freely in the electrolyte, the ionic conductivity will decrease, and the ion transmission speed will slow down, resulting in an increase in the internal resistance of the battery and affecting the battery life.
[0041] In some embodiments, the concentration of the additive in the electrolyte is 0.1 mM / L to 50 mM / L.
[0042] In one embodiment of the present application, a method for preparing an aqueous zinc ion battery electrolyte is provided, wherein a zinc salt is added to deionized water at 25°C and stirred until fully dissolved to obtain a basic zinc salt electrolyte, and then an additive is added to the obtained basic zinc salt electrolyte, and then stirred until fully dissolved to obtain an electrolyte modified with a borate derivative of an aqueous zinc ion battery.
[0043] Taking the preparation of an electrolyte composed of 5mM / L triethanolamine borate (TEAB) as an additive, 2mol / L zinc perchlorate (Zn(ClO4)2) as an electrolyte salt, and deionized water as a solvent as an example, at 25°C, 3.7238g of zinc perchlorate was added to 5mL of deionized water and stirred until fully dissolved to obtain a basic zinc perchlorate electrolyte with a concentration of 2mol / L, and then 0.0039g of triethanolamine borate electrolyte additive was added to the basic zinc sulfate electrolyte, and stirred until fully dissolved to obtain an electrolyte modified by borate derivatives of an aqueous zinc ion battery.
[0044] In one embodiment of the present application, an application of an aqueous zinc ion battery electrolyte is provided, and the aqueous zinc ion battery electrolyte or the electrolyte obtained by the preparation method is used in a Zn / / Zn symmetric battery, a Zn / / Cu half-cell or an aqueous zinc ion full battery.
[0045] In one embodiment of the present application, an aqueous zinc battery is provided, comprising a battery shell, a positive electrode, a diaphragm, an electrolyte, a negative electrode, a gasket and a spring, wherein the positive electrode and the negative electrode are relatively arranged in the battery shell, the electrolyte is arranged in the battery shell, the diaphragm is arranged in the electrolyte between the positive electrode and the negative electrode, and the gasket and the spring are arranged in the battery shell; the battery shell is CR2025, the positive electrode and the negative electrode are both high-purity zinc foil, the thickness of the high-purity zinc foil is 0.02-0.1mm, and the diameter is 12-16mm, the diaphragm is a glass fiber diaphragm, the diameter of the diaphragm is 16mm, and the amount of the electrolyte is 80-150μL; the battery is pressurized to 50MPa, and the pressure is maintained for 10 to 30s to complete the assembly of the Zn / / Zn symmetrical battery.
[0046] In one embodiment of the present application, an aqueous zinc battery is provided, comprising a battery shell, a positive electrode, a diaphragm, an electrolyte, a negative electrode, a gasket and a spring, wherein the positive electrode and the negative electrode are relatively arranged in the battery shell, the electrolyte is arranged in the battery shell, the diaphragm is arranged in the electrolyte between the positive electrode and the negative electrode, and the gasket and the spring are arranged in the battery shell; the battery shell is CR2025, the positive electrode is a high-purity copper foil with a thickness of 5-20um and a diameter of 12-16mm, the negative electrode is a high-purity zinc foil with a thickness of 0.02-0.1mm and a diameter of 12-16mm, the diaphragm is a glass fiber diaphragm with a diameter of 16mm, and the amount of the electrolyte is 80-150μL; the battery is pressurized to 50MPa, and the pressure is maintained for 10 to 30s to complete the assembly of the Zn / / Cu half-cell.
[0047] In one embodiment of the present application, an aqueous zinc battery is provided, comprising a battery shell, a positive electrode, a diaphragm, an electrolyte, a negative electrode, a gasket and a spring, wherein the positive electrode and the negative electrode are arranged relatively in the battery shell, the electrolyte is arranged in the battery shell, the diaphragm is arranged in the electrolyte between the positive electrode and the negative electrode, and the gasket and the spring are sequentially arranged in the battery shell; the base material of the positive electrode is a stainless steel mesh, on which the positive electrode material is cast, the negative electrode is one of high-purity zinc foil, zinc powder and foamed zinc, with a thickness of 0.02-0.1 mm and a diameter of 12-16 mm, the diaphragm is a glass fiber diaphragm with a diameter of 16 mm, the battery shell model is CR2025, and the electrolyte is used in an amount of 80-150 μL; the battery is pressurized to 50 MPa, and the pressure is maintained for 10 to 30 seconds to complete the assembly of the full battery.
[0048] The function of the spring is to provide a certain elastic pressure inside the battery to ensure good contact between the positive and negative electrodes of the battery and the external circuit. The thickness is usually 1.1mm or 1.2mm. The thickness of the gasket is usually 0.5mm or 1.0mm, which is used to adjust the internal space structure of the battery to improve the performance of the battery. The battery shell is CR2025, "20" represents that the diameter of the battery is 20mm, and the last two digits "25" represent that the thickness of the battery is 2.5mm. The thickness of the zinc sheet is usually 0.02mm, 0.05mm, 0.08mm, or 0.1mm. The diameter of the zinc electrode is usually 12mm or 16mm.
[0049] In some embodiments, the positive electrode material is one of iodine, manganese-based oxides, vanadium-based oxides, Prussian blue analogs, carbon felt, or graphite felt.
[0050] In some embodiments, the positive electrode is prepared by mixing the positive electrode material, Ketjen black and PVDF binder with NMP solvent in a weight ratio of 7:2:1 or 8:1:1 to form a uniform slurry, casting the slurry on a stainless steel wire mesh, and finally vacuum drying in a 40°C oven for 24 hours.
[0051] In some embodiments, the loading amount of the positive electrode material on the substrate material is about 1.5 to 2.0 mg·cm -2 .
[0052] Example
[0053] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0054] A water-based zinc ion battery electrolyte comprises a solvent, a zinc salt and an additive. The electrolyte additive is selected from borate compounds such as trimethyl borate, triethyl borate, tri(trimethylsilyl) borate, diethanolamine borate, triethanolamine borate, amino alcohol borate, etc.; the electrolyte salt is selected from one or more of ZnSO4, ZnCl2, Zn(ClO4)2, Zn(NO3)2, Zn(CF3SO3)2, Zn(CH3COO)2 and Zn(TFSI)2; and the solvent is deionized water.
[0055] In a specific embodiment, the concentration of zinc salt in the electrolyte can be any one of 0.5mol / L, 1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L, 3mol / L, and a range consisting of any two thereof. The proportion of the additive in the electrolyte in the electrolytic concentration can be, but is not limited to, 0.1mM / L, 0.5mM / L, 1mM / L, 5mM / L, 10mM / L, 15mM / L, 20mM / L, 25mM / L, 30mM / L, 35mM / L, 40mM / L, 45mM / L, 50mM / L.
[0056] The preparation of the electrolyte is based on the preparation of an electrolyte consisting of 5 mM / L triethanolamine borate (TEAB) as an additive, 2 mol / L zinc perchlorate (Zn(ClO4)2) as an electrolyte salt, and deionized water as a solvent. At 25°C, 3.7238 g of zinc perchlorate is added to 5 mL of deionized water and stirred until fully dissolved to obtain a basic zinc perchlorate electrolyte with a concentration of 2 mol / L. Then, 0.0039 g of triethanolamine borate electrolyte additive is added to the obtained basic zinc sulfate electrolyte, and then stirred until fully dissolved, wherein the concentration of triethanolamine borate in the electrolyte is 5 mM / L, thereby obtaining a triethanolamine borate-modified electrolyte for aqueous zinc ion batteries.
[0057] Preparation and testing of Zn / / Zn symmetric cells:
[0058] Assemble a Zn / / Zn symmetrical battery using 2mol / L zinc perchlorate and an electrolyte with 5mM / L triethanolamine borate additive. Assemble a Zn / / Zn symmetrical battery: The positive and negative electrode shells used are both CR2025, the positive and negative electrodes are both high-purity zinc foil (thickness 0.1mm, diameter 12mm), the diaphragm is a glass fiber diaphragm (diameter 16mm), and the electrolyte is 80μL. The battery assembly order is positive electrode shell-zinc foil-diaphragm-electrolyte-zinc foil-gasket-shrapnel-negative electrode shell, and then the battery is pressurized to 50MPa and maintained for 10 to 30s. The preparation of the Zn / / Zn symmetrical battery is completed. Then at 1mA / cm 2 and 1mAh / cm 2 , 5mA / cm 2 and 5mAh / cm 2 , 10mA / cm 2 and 10mAh / cm 2 The assembled symmetrical battery was subjected to constant current charge and discharge tests at current density and surface capacity.
[0059] Since the battery can operate stably at high current density, it can achieve rapid charging and discharging of the battery, shorten the charging time, and improve the battery efficiency. Large surface capacity can store more electricity per unit electrode area and achieve high energy density.
[0060] in accordance with Figure 7 According to the test data of symmetrical batteries, TEAB additive can enable aqueous zinc-ion symmetrical batteries to provide more stable energy output at higher current density and surface capacity.
[0061] Preparation and testing of Zn / / Cu half-cell:
[0062] Use 2mol / L zinc perchlorate and an electrolyte with 5mM / L triethanolamine borate additive to assemble the Zn / / Cu half-cell. Assemble the Zn / / Cu symmetrical battery: the positive and negative shells used are both CR2025, the positive electrode is a high-purity copper foil (8um thickness, 12mm diameter), the negative electrode is a high-purity zinc foil (0.1mm thickness, 12mm diameter), the diaphragm is a glass fiber diaphragm (16mm diameter), and the electrolyte is 80μL. The battery assembly order is positive electrode shell-copper foil-diaphragm-electrolyte-zinc foil-gasket-shrapnel-negative electrode shell, and then the battery is pressurized to 50MPa and maintained for 10 to 30s. The preparation of the Zn / / Cu half-cell is completed. Then at 1mA / cm 2 and 1mAh / cm 2 , 5mA / cm 2 and 5mAh / cm 2 , 10mA / cm 2 and 10mAh / cm 2 The assembled half-cell was subjected to constant current charge and discharge tests at current density and surface capacity.
[0063] Since the nucleation and growth process of the first cycle has a great influence on the battery, the nucleation and growth process of Zn is generally analyzed by assembling Zn / / Cu half-cells and selecting the data of the first cycle.
[0064] from Figure 8 It can also be seen that zinc deposition consists of two parts: rapid nucleation and continuous growth. During nucleation, zinc ions quickly aggregate and reduce at the active sites, causing their activity to drop sharply, resulting in rapid changes in the electrode potential. During continuous growth, zinc ions are deposited on existing nuclei, and the reaction proceeds at a relatively stable rate, which does not cause large fluctuations in voltage.
[0065] Preparation and testing of Zn / / I2 full cells:
[0066] The aqueous zinc ion full battery was assembled using an electrolyte containing 2 mol / L zinc perchlorate and 5 mM / L triethanolamine borate additive. The construction of the aqueous zinc ion full battery includes the above-mentioned triethanolamine borate modified electrolyte, positive electrode material, negative electrode material, diaphragm, gasket and shrapnel. The positive electrode material is one of iodine, manganese-based oxide, vanadium-based oxide, Prussian blue analog, carbon felt or graphite felt. The negative electrode material is one of zinc foil, zinc powder and zinc foam. The diaphragm is a glass fiber diaphragm. Assembly of Zn / / I2 full battery: The positive and negative electrode shells used are both CR2025, the positive electrode matrix material is stainless steel mesh, and the preparation of the positive electrode material: Taking I2 as an example, I2, Ketjen black and PVDF binder are mixed with NMP solvent in a weight ratio of 7:2:1 to form a uniform slurry. The slurry is cast on a stainless steel wire mesh and finally vacuum dried in an oven at 40°C for 24 hours. The loading amount of I2 cathode electrode material is about 1.5-2.0 mg cm -2 The negative electrode is a high-purity zinc foil (thickness 0.1mm, diameter 12mm), the diaphragm is a glass fiber diaphragm (diameter 16mm), and the electrolyte is 80μL. The battery assembly order is positive electrode shell-positive electrode-diaphragm-electrolyte-zinc foil-gasket-shrapnel-negative electrode shell, and then the battery is pressurized to 50MPa and maintained for 10 to 30s. The preparation of the Zn / / I2 full battery is completed. The assembled battery is subjected to constant current charge and discharge tests.
[0067] like Fig. 9 The coulombic efficiency CE of the aqueous zinc-iodine full cell with an addition amount of 5mM / L TEAB is close to 100%.
[0068] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. An aqueous zinc ion battery electrolyte, characterized in that The invention comprises a solvent, a zinc salt and an additive, wherein the additive is a borate ester derivative.
2. An aqueous zinc ion battery electrolyte according to claim 1, characterized in that: The borate derivatives are one or more of trimethyl borate, triethyl borate, tri(trimethylsilyl) borate, diethanolamine borate, triethanolamine borate, and amino alcohol borate.
3. An aqueous zinc ion battery electrolyte according to claim 1, characterized in that: The zinc salt is one or more of ZnSO4, ZnCl2, Zn(ClO4)2, Zn(NO3)2, Zn(CF3SO3)2, Zn(CH3COO)2 and Zn(TFSI)2; the solvent is deionized water; the concentration of the zinc salt is 0.5 mol / L to 3 mol / L.
4. An aqueous zinc ion battery electrolyte according to claim 1, characterized in that: The concentration of the additive in the electrolyte is 0.1 mM / L to 50 mM / L.
5. A method for preparing an aqueous zinc ion battery electrolyte according to any one of claims 1 to 4, characterized in that: At room temperature, a zinc salt is added to deionized water and stirred until fully dissolved to obtain a basic zinc salt electrolyte, and then an additive is added to the obtained basic zinc salt electrolyte, and then stirred until fully dissolved to obtain a borate derivative-modified electrolyte for an aqueous zinc ion battery.
6. Application of an aqueous zinc ion battery electrolyte, the application of the aqueous zinc ion battery electrolyte according to any one of claims 1 to 4 or the electrolyte obtained by the preparation method according to claim 5 in a Zn / / Zn symmetrical battery, a Zn / / Cu half-cell or an aqueous zinc ion full battery.
7. An aqueous zinc battery, comprising a battery shell, a positive electrode, a diaphragm, an electrolyte, a negative electrode, a gasket and a spring, wherein the positive electrode and the negative electrode are relatively arranged in the battery shell, the electrolyte is the aqueous zinc ion battery electrolyte according to any one of claims 1 to 4 or the electrolyte obtained by the preparation method according to claim 5, the electrolyte is arranged in the battery shell, the diaphragm is arranged in the electrolyte between the positive electrode and the negative electrode, and the gasket and the spring are arranged in the battery shell; the battery shell is CR2025, the positive electrode and the negative electrode are both high-purity zinc foil, the thickness of the high-purity zinc foil is 0.02-0.1mm, and the diameter is 12-16mm, the diaphragm is a glass fiber diaphragm, the diameter of the diaphragm is 16mm, and the amount of the electrolyte is 80-150μL; the battery is pressurized to 50MPa, and the pressure is maintained for 10 to 30s to complete the assembly of the Zn / / Zn symmetrical battery.
8. An aqueous zinc battery, comprising a battery shell, a positive electrode, a diaphragm, an electrolyte, a negative electrode, a gasket and a spring, the positive electrode and the negative electrode are relatively arranged in the battery shell, the electrolyte is arranged in the battery shell, the electrolyte is the aqueous zinc ion battery electrolyte according to any one of claims 1 to 4 or the electrolyte obtained by the preparation method according to claim 5, the diaphragm is arranged in the electrolyte between the positive electrode and the negative electrode, and the gasket is provided with a spring; the battery shell is CR2025, the positive electrode is a high-purity copper foil with a thickness of 5-20um and a diameter of 12-16mm, the negative electrode is a high-purity zinc foil with a thickness of 0.02-0.1mm and a diameter of 12-16mm, the diaphragm is a glass fiber diaphragm with a diameter of 16mm, and the amount of the electrolyte is 80-150μL; the battery is pressurized to 50MPa, and the pressure is maintained for 10 to 30s to complete the assembly of the Zn / / Cu half-cell.
9. An aqueous zinc battery, comprising a battery shell, a positive electrode, a diaphragm, an electrolyte, a negative electrode, a gasket and a spring, wherein the positive electrode and the negative electrode are arranged relative to each other in the battery shell, the electrolyte is arranged inside, the electrolyte is the aqueous zinc ion battery electrolyte according to any one of claims 1 to 4 or the electrolyte obtained by the preparation method according to claim 5, the diaphragm is arranged in the electrolyte between the positive electrode and the negative electrode, and the gasket is provided with a spring; the base material of the positive electrode is a stainless steel mesh, the positive electrode material is cast on the stainless steel mesh, the negative electrode is one of high-purity zinc foil, zinc powder and foamed zinc, with a thickness of 0.02-0.1 mm and a diameter of 12-16 mm, the diaphragm is a glass fiber diaphragm with a diameter of 16 mm, the battery shell model is CR2025, and the electrolyte is used in an amount of 80-150 μL; the battery is pressurized to 50 MPa, and the pressure is maintained for 10 to 30 seconds to complete the assembly of the Zn / / I2 full battery.
10. The aqueous zinc battery according to claim 9, characterized in that: The positive electrode material is one of iodine, manganese-based oxide, vanadium-based oxide, Prussian blue analog, carbon felt or graphite felt; the loading amount of the positive electrode material on the substrate material is about 1.5-2.0 mg·cm -2 .